Vaksinasi COVID-19 dan Polemik Raffi Ahmad dalam Framing Pemberitaan Media Tirto.id dan Detik.com - Khumaid Akhyat Sulkhan (School of Communication Science and Media Business, 2021)
This study aims to analyze how the media Tirto.id and Detik.com frame the violation of Raffi Ahmad's health protocol after receiving the first batch of Covid-19 vaccinations, using the framing analysis approach developed by Robert N. Entman. The concept of Entman framing analysis is often used to examine how the media selects and accentuates certain realities before publishing them as news. Entman has four approaches in the concept of analysis to study news as text, namely by looking at how the media defines problems, diagnosing causes, then making moral decisions, and offering treatment recommendations. In this study, researchers found that Tirto.id not only troublesome Raffi Ahmad for violating health protocols after being vaccinated, but also troublesome President Joko Widodo era, which still uses celebrities or influencers to support its policies, even though it has resulted in weaknesses. Meanwhile, Detik.com tends to inflict all problems on Raffi Ahmad and has so far stopped on emphasizing social sanctions against these celebrities as punishment. Keywords: framing analysis, Covid-19 vaccine, Raffi Ahmad, media construction